2006
DOI: 10.1107/s1600536806047258
|View full text |Cite
|
Sign up to set email alerts
|

Goethite, α-FeO(OH), from single-crystal data

Abstract: Key indicatorsSingle-crystal X-ray study T = 273 K Mean (e-O) = 0.001 Å R factor = 0.019 wR factor = 0.052 Data-to-parameter ratio = 21.0 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 15 publications
4
87
2
3
Order By: Relevance
“…Microscopic observations have also clarified the thermal decomposition of goethite into hematite through the formation mechanism of slit-like micropores [12]. In this case, the slits are generated along the goethite [001] G direction, where the crystal is defined by the orthorhombic space group Pbnm, with lattice constants of a G = 4.5979 Å, b G = 9.9510 Å, and c G = 3.0175 Å [12][13][14]. Structural investigation on the thermal decomposition of goethite was carried out using X-ray and electron diffraction with high-resolution transmission electron microscope (TEM) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic observations have also clarified the thermal decomposition of goethite into hematite through the formation mechanism of slit-like micropores [12]. In this case, the slits are generated along the goethite [001] G direction, where the crystal is defined by the orthorhombic space group Pbnm, with lattice constants of a G = 4.5979 Å, b G = 9.9510 Å, and c G = 3.0175 Å [12][13][14]. Structural investigation on the thermal decomposition of goethite was carried out using X-ray and electron diffraction with high-resolution transmission electron microscope (TEM) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Proper phase identification requires calibration of the instrumental geometry; in this case, this was accomplished through the diffraction patterns of Si and Al 2 O 3 . Table 4 shows the main crystalline phases observed in the corrosion layer and the d-spacing and Miller indices of their high-intensity finger-print reflections that were used to identify them [40,41]. Other phases usually found as corrosion products display only high angle, low d-spacing reflections, which are difficult to use phase identification due to strong peak overlap at low d-spacings.…”
Section: Phase Distributionmentioning
confidence: 99%
“…8(a) and (b), which were obtained by integration over the full range of 2θ measured]. This was done using the (101) reflection at d-spacing 4.20 Å for goethite [40] and (512) reflection at d-spacing 1.63 Å for akaganeite [41]. Fig.…”
Section: Phase Distributionmentioning
confidence: 99%
“…The atomic radii of Tc(IV) and Fe(III) are also closely related in size (78.5 vs. 69 to 78.5 pm, (a) respectively), and both are octahedral (6-fold) coordinated (Huheey et al 1993), so a coupled substitution scheme is possible. The atomic structure of goethite, recently determined by Yang et al (2006), is shown in Figure 2.5. On the other hand, examining the reduced run products with X-ray absorption spectroscopy (XAS) methods (briefly described in Appendix A) has revealed that the 99 Tc-bearing phase is a separate, reduced Tc(IV) oxide phase and may not be substituting for Fe(III)-O in the host ferric oxyhydroxide phase (Burke et al 2006, Fredrickson et al 2004, Fredrickson et al 2009, Morris et al 2008, Peretyazhko et al 2008a, Watson et al 2001, Wharton et al 2000, Zachara et al 2007).…”
mentioning
confidence: 99%
“…On the one hand, substituting Tc(IV) for Fe(III) in goethite, for example, is plausible because the Tc(IV)-O and Fe(III)-O bond lengths are similar (1.99 and 2.026 Å, respectively) (Yang et al 2006). The atomic radii of Tc(IV) and Fe(III) are also closely related in size (78.5 vs. 69 to 78.5 pm, (a) respectively), and both are octahedral (6-fold) coordinated (Huheey et al 1993), so a coupled substitution scheme is possible.…”
mentioning
confidence: 99%